Soil carbon dynamics : an integrated methodology - Kutsch, Werner, 1960-; Bahn, Michael; Heinemeyer, Andreas (Cambridge, UK : Cambridge University Press, 2009)
Carbon stored in soils represents the largest terrestrial carbon pool and factors affecting this will be vital in the understanding of future atmospheric CO2 concentrations. This book provides an integrated view on measuring and modelling soil carbon dynamics.
Includes bibliographical references and index.
Keywords: Soils -- Carbon content -- Measurement; Greenhouse effect, Atmospheric; Carbon cycle (Biogeochemistry)